PENGARUH BUDAYA ORGANISASI DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI - Kuncoro, Muhamad Amin (Sekolah Tinggi Ilmu Ekonomi Atma Bhakti, 2011)
The purpose of this study was to know the effect of organizational culture and leadership style toward employee job performance with organizational as mediating variable in PG Rejo Agung Baru Madiun. Sample in this research is 84 people, using proportional random sampling method. Examination of validity used correlation of moment product and examination of reliability used alpha cronbach. Data in this research analyzed by classic assumption test, path analysis, multiple linier regression, t test, F test and R2 . Based on data analysis, the result as bellow: 1)leadership style has not significant influence to job performance, 2)organizational culture has positive and significant influence to job performance, 3)leadership style has significant influence to organizational commitment, 4) organizational culture has significant influence to organizational commitment, 5) organizational commitment has not significant influence to job performance, 6)organizational commitment has not mediated the influence leadership style to job performance, 7)organizational commitment has not mediated the influence organizational culture to job performance,